2013
DOI: 10.1016/s1734-1140(13)71490-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of octane derivatives on activity of the volume-regulated anion channel in rat pancreatic β-cells

Abstract: Abstract:Background: Saturated free fatty acids (FFAs) have a dual action on pancreatic b-cells, consisting of an initial enhancement and subsequent suppression of glucose-induced electrical activity and insulin release. These stimulatory and inhibitory effects have been attributed, at least in part, to the activation and inhibition, respectively, of the volume-regulated anion channel (VRAC) by FFAs. Both effects were independent of their metabolism. We have now investigated the effects of related aliphatic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…Two distinct IP3 receptor inhibitors either diminished the OA-induced increase in [Ca 2+ ] i in insulinoma MIN6 cells 35 or abolished the OA-induced increase in [Ca 2+ ] i in Sur1 -/mouse islets (this study). Studies by Best et al showed that OA caused a transient potentiation of glucose-induced electrical activity and a transient increase in VSAC activity in rat βcells, 32 also consistent with our observations. However, the electrophysiologic studies by Best et al showed that after the initial activation of VSACs, OA caused a gradual hyperpolarization and a prolonged inhibition of electrical activity, 32 a phenomenon which we did not observe in our mouse islet measurements.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Two distinct IP3 receptor inhibitors either diminished the OA-induced increase in [Ca 2+ ] i in insulinoma MIN6 cells 35 or abolished the OA-induced increase in [Ca 2+ ] i in Sur1 -/mouse islets (this study). Studies by Best et al showed that OA caused a transient potentiation of glucose-induced electrical activity and a transient increase in VSAC activity in rat βcells, 32 also consistent with our observations. However, the electrophysiologic studies by Best et al showed that after the initial activation of VSACs, OA caused a gradual hyperpolarization and a prolonged inhibition of electrical activity, 32 a phenomenon which we did not observe in our mouse islet measurements.…”
Section: Discussionsupporting
confidence: 93%
“…Studies by Best et al showed that OA caused a transient potentiation of glucose-induced electrical activity and a transient increase in VSAC activity in rat βcells, 32 also consistent with our observations. However, the electrophysiologic studies by Best et al showed that after the initial activation of VSACs, OA caused a gradual hyperpolarization and a prolonged inhibition of electrical activity, 32 a phenomenon which we did not observe in our mouse islet measurements. Nevertheless, our results generally support the concept that OA may play its potentiating effect on insulin secretion via VSACs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is added to some foods as a food flavor and is also used as a raw material for the production of caprylaldehyde and caprylic acid [ 38 , 39 ]. Some studies have shown that octanol has a two-way regulatory effect on the membrane potential of rat pancreatic β-cells and enhances the activity of volume-regulated anion channels [ 40 ]. Caprylic acid is a monocarboxylate saturated fatty acid involved in ketogenic metabolism.…”
Section: Discussionmentioning
confidence: 99%